Engineering Nanoscale Metal‐Organic Frameworks for Heterogeneous Catalysis. Issue 6 (17th March 2021) - Zhang, Xiaofei; Han, Jianyu; Guo, Jun; Tang, Zhiyong
Abstract : Metal‐organic frameworks (MOFs) are porous crystalline materials composed of metal ions (or clusters) and organic ligands. Targeted preparation of nanoscale MOFs has been successfully achieved through numerous synthetic methods and is beneficial to improve the utilization of catalytic sites. On one hand, the dynamic bonds and rich selection of both metal centers and organic molecules enable broadening the types and functions of MOFs, thus offering the basis for rational design of heterogeneous catalysts at the molecular level. On the other hand, the reversible nature of connections between metal centers and organic ligands brings serious challenges about its stability under harsh reaction conditions. To optimize the catalytic performance of MOFs, considerable efforts have been devoted to tune the chemical environment of active sites by introducing electronic or channel confinement effect as well as controlling their size growth at nanoscale for increasing the surface coordination unsaturated sites. In this review, the state‐of‐the‐art development of nanoscale MOFs is summarized and particular focus is placed on regulation strategies of catalytic sites. The authors also propose the current challenges, the problems awaiting to be solved and opportunities in the future. Abstract : Nanoscale metal–organic frameworks (MOFs) are widely utilized as the efficient heterogeneous catalysts due to abundant active sites and tunable coordination environment. Furthermore, the catalytic activity of MOFs is regulated at the molecular level through regulating electronic state of the active center, constructing the environment of pores, and postmodifying active sites.